A mixed‐methods needs assessment to identify pharmacology education objectives for emergency medicine residents - Ashley C. Rider; Brian T. Dang; Holly A. Caretta‐Weyer; Kimberly A. Schertzer; Michael A. Gisondi (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Medication errors represent a significant threat to patient safety. Pharmacotherapy is one of the 23 Accreditation Council of Graduate Medical Education milestones for emergency medicine, yet there is minimal understanding of what content should be prioritized during training. The study aim was to develop objectives for a patient‐safety focused pharmacology curriculum for emergency medicine residents. Methods We incorporated data from a de‐identified safety event database and survey responses of 30 faculty and clinical pharmacists at a single‐site suburban university hospital with 24‐hour emergency medicine pharmacists and an annual volume of approximately 70,000. We reviewed the database to quantify types and severity of medication errors over a 5‐year period for a total of 370 errors. Anonymous surveys included categorical items that we analyzed with descriptive statistics and short answer questions that underwent thematic analysis by 2 coders. We summarized all data sources to identify curriculum gaps. Results Common medication errors reported in our database were wrong dose (43%) and computer order entry errors (14%). Knowledge gaps were medication cost (63%), pregnancy risk information (60%), antibiotic stewardship (53%), interactions (47%), and side effects (47%). Qualitative analysis revealed the need to optimize computer order entry, understand the scope of critical medications, use references, and consult pharmacists. Integration of data suggested specific medications should be covered in curricular efforts, including antibiotics, analgesics, sedatives, and insulin. Conclusion We developed objectives of pharmacology topics to prioritize during emergency medicine training to enhance prescribing safety. This study is limited due to its small sample and single institution source of data. Future studies should investigate the impact of pharmacology curriculum on minimizing clinical errors.